Cycas revoluta, Sago Palm - Robert J. Northrop; Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 254, a 2-page fact sheet by Robert J. Northrop, Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this evergreen cycad native to the tropical islands of southern Japan, but grows well in the subtropics of the United States — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.